2019
DOI: 10.1155/2019/9151070
|View full text |Cite
|
Sign up to set email alerts
|

Adenine Inhibits the Growth of Colon Cancer Cells via AMP-Activated Protein Kinase Mediated Autophagy

Abstract: Background. Adenine is involved in a variety of cell biological processes and has been explored for pharmacological uses. Its therapeutic use for managing cancer is of great interest. In the present study, we investigated the anticancer effects of adenine and the underlying mechanism in colon cancer cells. Methods. Cell viability was measured using the MTT assay. Levels of phosphorylation and protein expression were determined using western blotting. qPCR was carried out to determine the changes in mRNA expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…In addition to energy regulation, AMPK also governs the important cellular physiological activities including cell proliferation, cell growth, and autophagy (18,19). Accordingly, AMPK has been recognized as an important anticancer target in suppressing the growth of different carcinoma cells such as 786-O (10), K562 (11), and HT29 (20). Similarly, we also observe that adenine-induced AMPK activation play an important role in the growth inhibition of HepG2 and SK-Hep-1 cells which express wild-type p53.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to energy regulation, AMPK also governs the important cellular physiological activities including cell proliferation, cell growth, and autophagy (18,19). Accordingly, AMPK has been recognized as an important anticancer target in suppressing the growth of different carcinoma cells such as 786-O (10), K562 (11), and HT29 (20). Similarly, we also observe that adenine-induced AMPK activation play an important role in the growth inhibition of HepG2 and SK-Hep-1 cells which express wild-type p53.…”
Section: Discussionmentioning
confidence: 99%
“…NAM further was found to arrest the cancer microenvironment by suppression of cancer associated fibroblasts (CAF) proliferation through increasing the cellular oxidative stress in vitro (Hassan et al, 2020[ 14 ]). Adenine is a purine derivative synthesized in human liver and also found in brewer's yeast and vegetables (Lai et al, 2019[ 21 ]) and detected in P. juliflora . It is pharmacologically used in several biological processes like cellular respiration, deoxyribonucleic acid (DNA) in protein synthesis and also as a component of the former nicotinamide (Lai et al, 2019[ 21 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Adenine is a purine derivative synthesized in human liver and also found in brewer's yeast and vegetables (Lai et al, 2019[ 21 ]) and detected in P. juliflora . It is pharmacologically used in several biological processes like cellular respiration, deoxyribonucleic acid (DNA) in protein synthesis and also as a component of the former nicotinamide (Lai et al, 2019[ 21 ]). Recently, adenine was strongly approved for inhibition of growth and proliferation of the colorectal cancerous cells through apoptotic and autophagic pathways of cell death (Lai et al, 2019[ 21 ]).…”
Section: Discussionmentioning
confidence: 99%
“…AMPK activation has also been linked with induction of cell cycle arrest and cell death (Vincent et al, 2015). Anti-tumor effects of adenine for colon (Han et al, 2017), cervical (Lai et al, 2019) and hepatic (Su et al, 2020) cancer cells are mediated from adenine-induced cell cycle arrest and AMPK activated. Therefore, the cytotoxic effect of adenine on melanoma cells shown here may be through AMPK activation of adenine in melanoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that adenine is cytotoxic to lymphoblast (Hershfield et al, 1977;Snyder et al, 1978) and has anti-tumor activity for colon (Han et al, 2017), cervical (Lai et al, 2019) and hepatic (Su et al, 2020) cancer cells.…”
Section: Original Articlementioning
confidence: 97%